Palladium-Catalyzed Asymmetric 1,4-Addition of Diarylphosphines to α,β-Unsaturated Sulfonamides - Dai, Guo-Fa; Song, Yu-Chuan; Xiao, Fanhua; Duan, Wei-Liang (Synthesis, 2018)
A pincer palladium-catalyzed asymmetric 1,4-addition of diarylphosphines to α,β-unsaturated sulfonamides was realized for the synthesis of chiral sulfonamide phosphines with up to 98% ee under mild conditions.
Keywords: α,β-unsaturated sulfonamides; asymmetric 1,4-addition; pincer palladium catalyst; chiral phosphine